2010
DOI: 10.1071/cp10003
|View full text |Cite
|
Sign up to set email alerts
|

Novel barley (Hordeum vulgare L.) germplasm resistant to acidic soil

Abstract: Improving the resistance of barley (Hordeum vulgare L.) to acidic soils is an important goal of several barley breeding programs around the world. The identification and utilisation of novel barley sources resistant to aluminium (Al) may provide a significant and rapid advance towards that goal. Barley standards and screening protocols for selecting barley germplasm resistant to Al in nutrient solution and acidic soil were reevaluated. The assays used were quantitative in nature and were suitable for genotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…This stimulation of growth in acid conditions by low levels of Al 3+ has been observed previously and is interpreted as Al 3+ alleviating H + toxicity ( Kinraide et al , 1992 ). Moroni et al (2010) screened a range of cereal genotypes for Al 3+ tolerance and concluded that the rankings differed between hydroponic and field trials because barley appeared more tolerant in soil than the hydroponic screens. While the present study found broad agreement between the results in hydroponics and short soil experiments, longer field trials will be necessary to assess how effective these transgenes are in improving grain yield on acid soils.…”
Section: Discussionmentioning
confidence: 99%
“…This stimulation of growth in acid conditions by low levels of Al 3+ has been observed previously and is interpreted as Al 3+ alleviating H + toxicity ( Kinraide et al , 1992 ). Moroni et al (2010) screened a range of cereal genotypes for Al 3+ tolerance and concluded that the rankings differed between hydroponic and field trials because barley appeared more tolerant in soil than the hydroponic screens. While the present study found broad agreement between the results in hydroponics and short soil experiments, longer field trials will be necessary to assess how effective these transgenes are in improving grain yield on acid soils.…”
Section: Discussionmentioning
confidence: 99%
“…Barley is among the most Al 3+ -sensitive cereal crops and, although genotypic variation exists within this species, Al 3+ -tolerant genotypes are more sensitive than Al 3+ -tolerant wheat plants. A seedling-based screen of diverse barley genotypes identified the cultivars Kearney and 'Golden Promise' as being Al 3+ sensitive and 'Dayton' and several Japanese cultivars as being among the most tolerant (Moroni et al, 2010). Hexaploid wheat has a greater variation in Al 3+ tolerance than barley, with differences in root growth that can vary by .10-fold in short-term growth assays or in field screens (Rengel and Jurkic, 1992;Bona et al, 1993;Ryan et al, 1995;Pinto-Carnide and Guedes-Pinto, 1999;Garvin and Carver, 2003;Tang et al, 2003;Raman et al, 2008;Dai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Even barley, which is considered one of the most Al 3+ -sensitive of the small-grained Triticeae, displays significant genotypic variability. A seedling-based screen of barley lines in the South and East Asian Barley Core Collection identified Kearney and Golden Promise as sensitive to Al 3+ while Dayton and several Japanese cultivars (Honen, Ohichi and Zairai Tanbo) were among the most resistant (Moroni et al 2010). A greater variation occurs in hexaploid or bread wheat where differences in root growth can vary by ten-fold or more in short-term growth assays or in field screens (Bona et al 1993;Cosic et al 1994;Dai et al 2009;Foy 1996;Garvin and Carver 2003;Pinto-Carnide and Guedes-Pinto 1999;Raman et al 2008;Rengel and Jurkic 1992;Ryan et al 1995a;Tang et al 2003).…”
Section: Natural Variationsmentioning
confidence: 99%